The Influence of Asymmetric Load Distribution on V-Belt and Pulley Transmission in Belt Conveyor Systems - Ade Irvan Tauvana; Syafrizal Syafrizal; Gilang Ramadhan (Jurnal Rekayasa Mesin, 2026)
Belt conveyor performance is highly dependent on the uniformity of load distribution along the belt. In practical applications—particularly in industrial, retail, and airport environments spatial limitations often force systems to operate under asymmetric loading conditions. This situation introduces a technical problem because uneven load distribution can alter contact pressure, increase belt misalignment, and accelerate mechanical wear. Although numerous studies have explored belt tensioning, pulley design, and material durability, only limited research specifically addresses the influence of asymmetric loads on slip behavior, indicating a gap in understanding the dynamic response of pulley–belt transmission systems. This study aims to experimentally evaluate the effect of asymmetric load distribution on slip characteristics in a conveyor belt transmission. The experimental setup involved shifting the load to the left or right side of the belt, while pulley speed was measured using a PLC-based monitoring system integrated with an inverter controlling a three-phase induction motor. Measurements were conducted at operating frequencies of 5–8 Hz under both symmetric and asymmetric loading scenarios. Results show that under symmetric loading, slip decreased by 0.632% across the tested speed range. Under asymmetric loading, the slip reduction increased to 1%, demonstrating that lateral load shifts generate higher local contact forces and temporarily enhance local transmission efficiency. However, this condition also has the potential to cause belt instability and reduce the lifespan of mechanical components. In conclusion, asymmetric loading significantly affects slip performance, offering short-term efficiency benefits but posing long-term operational risks. These findings provide important practical insight for optimizing conveyor systems operating in environments with constrained or non-uniform load conditions.